Clinical InvestigationsA comparison of dose distribution from Manchester-style and Fletcher-style intracavitary brachytherapy applicator systems in cervical cancer - Basu, Bishan; Basu, Swapnendu; Chakraborti, Bikramjit; Ghorai, Suman; Gupta, Phalguni; Ghosh, Sajal; Ghosh, Koushik; J., Jayanti (Journal of Contemporary Brachytherapy, 2012)
Purpose : During intracavitary brachytherapy (ICBT) for cervical cancer, the choice of applicator system remains rather arbitrary. However, as the applicator geometry may play an important role in dose distribution, thereby improving the therapeutic ratio, this study was conducted to compare the Manchester-style and Fletcher-style applicator systems. Material and methods: After completion of EBRT, 22 patients with cervical cancer (stage IIA-IIIB) underwent intracavitary brachytherapy. Two different types of applicators: Manchester-style and Fletcher-style were used for each patient for alternate insertions. The purpose was to compare the dose distribution obtained when two different applicators were applied to the same patient. CT based computerized treatment planning was done and dose was prescribed to point A. After optimization, height, width and thickness of the 100% isodose curve, as well as the 100% isodose volume were noted. Dose received by the urinary bladder and rectum were noted. Results: The 100% isodose volume and its maximum width were significantly greater (P value < 0.0001 in both occasions) when Manchester-style applicator was used. However, the dose received by 0.1 cc, 1.0 cc and 2.0 cc of the urinary bladder were all significantly greater (P value < 0.0001) with the Manchester-style applicator. No significant difference was found in rectal doses. Conclusions : The larger 100% isodose volume, as well as the greater width achieved with the use of Manchester-style applicator can be helpful in circumstances where the tumour is large in size. However, this must be balanced against the increased dose received by the urinary bladder.